2020
DOI: 10.1002/elan.202060198
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Determination of Caffeine Using Bimetallic Au−Ag Nanoparticles Obtained from Low‐cost Green Synthesis

Abstract: A novel caffeine sensor was constructed. The sensor is based on a platinum electrode (PtE) modified with polypyrrole (PPY) and green synthesized AgÀ Au bimetallic nanoparticles. The work further describes the synthesis of silver nanoparticles (AgNPs), gold nanoparticles (AuNPs), as well as AgÀ Au bimetallic nanoparticles (BMNPs) using the extract of citrus sinensis (sweet orange) peels. The nanoparticles were used to form nanocomposite material supported on polypyrrole (PPY) and, consequently used to modify Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…In addition, the work of Masibi et al [ 104 ] demonstrated the preparation of a platinum electrode modified with bimetallic gold and silver nanoparticles and polypyrrole (PPY/AgAuBMNPs). The data obtained by electrochemical methods showed that the newly developed sensor was suitable for the detection of CF ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the work of Masibi et al [ 104 ] demonstrated the preparation of a platinum electrode modified with bimetallic gold and silver nanoparticles and polypyrrole (PPY/AgAuBMNPs). The data obtained by electrochemical methods showed that the newly developed sensor was suitable for the detection of CF ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the results obtained in the papers published by Ferrag et al [ 97 ] and Masibi et al [ 104 ], it can be said that the electrode modification process should be another key parameter for selecting a suitable sensor. Both fabricated sensors, MWCNT-AuNP-CCE and PPY/AgAuBMNPs, show applicability in real samples ( Table 6 and Table 7 ) with low LOD values for CF, but Masibi and coworkers [ 104 ] chose a harmless modification process. In addition to obtaining good sensitivity, selectivity, and stability of the sensor, the authors should also work towards the use of environmentally friendly materials and substances in the modification processes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a sol‐gel process was utilized to create a molecularly imprinted siloxane film on a glassy carbon electrode modified with multiwall carbon nanotubes/vinyltrimethoxysilane, which showed a linear response range of 0.75 to 40 μM L −1 and a detection limit of 0.22 μM L −1 for caffeine. An electrochemical biosensor for the detection of caffien was also developed, which exhibited excellent sensitivity and selectivity [37–47] …”
Section: Introductionmentioning
confidence: 99%
“…An electrochemical biosensor for the detection of caffien was also developed, which exhibited excellent sensitivity and selectivity. [37][38][39][40][41][42][43][44][45][46][47] Methyl orange is an azo dye that causes harmful effects on aquatic life and human beings. Azo dyes are large synthetic dyes class containing an azo group with an aromatic system that includes a chemical substituent that makes them soluble in water.…”
Section: Introductionmentioning
confidence: 99%
“…Bimetallic nanoparticles have received great attention in the last years, as they exhibit outstanding properties in comparison with the corresponding monometallic forms. These unique properties include the tuned frequency shift of plasmon modes [1][2][3], the high catalytic activity towards hydrogen generation [4], the carbon dioxide reduction [5], and the reduction and oxidation of various chemical compounds such as nitrophenol [6], caffeine [7], benzyl alcohol [8], and formic acid [9]. Bimetallic nanoparticles with different shapes and structures have been reported such as nanoframes [9], nanoprisms [10], core-shell [1,11], nanoflowers [12], and hollow nanoparticles [13,14].…”
Section: Introductionmentioning
confidence: 99%